1992
DOI: 10.1111/j.1365-2044.1992.tb02266.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐controlled analgesia: a double‐blind study in burn patients

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…In the 5 acutely burned patients, morphine at a mean dose of 3.1 mg/h for a mean of 28.3 hours (range, 9.5-72 hours) was also reported to give good results. Choiniere et al (8) compared IV PCAmorphine to intermittent as-needed IV morphine in 24 adult burn patients in a double-blinded study. Although the amount of morphine was similar between study groups, the group receiving IV PCA-morphine reported better pain relief compared with the control group.…”
Section: Anesth Analgmentioning
confidence: 99%
“…In the 5 acutely burned patients, morphine at a mean dose of 3.1 mg/h for a mean of 28.3 hours (range, 9.5-72 hours) was also reported to give good results. Choiniere et al (8) compared IV PCAmorphine to intermittent as-needed IV morphine in 24 adult burn patients in a double-blinded study. Although the amount of morphine was similar between study groups, the group receiving IV PCA-morphine reported better pain relief compared with the control group.…”
Section: Anesth Analgmentioning
confidence: 99%
“…To this end, IV PCA has been shown to be safe and effective. 476 Absorption of IM and transdermal opioids is variable because of decreased tissue perfusion and uptake, which makes these routes unsuitable in this patient population. However, gastrointestinal absorption and emptying appear to be unchanged.…”
Section: Opioids In Patients With Burn Injurymentioning
confidence: 99%
“…To this end, IV PCA has been shown to be safe and effective. 312 The absorption of IM and transdermal opioids is variable due to decreased tissue perfusion and uptake, making these routes unsuitable in this patient population. Gastrointestinal absorption and emptying appear to be unchanged, however.…”
Section: Opioids In the Setting Of Burn Injurymentioning
confidence: 99%